A Rare Case Report of Giant Cell Tumor in Metacarpal Bone - Tarun Teja; Sandeep Shrivastava; Raghvendra Singh; Shreenivas Nalhe; Vinit Rathod (Journal of Orthopaedic Case Reports)
Introduction: Giant cell tumor (GCT), also known as osteoclastoma, is an osteolytic, predominantly benign yet locally aggressive neoplasm that manifests in young adults within the meta-epiphyseal region of long bones, specifically the distal femur, proximal tibia, distal radius, and proximal humerus, in that order of prevalence. GCT of the metacarpal (MC) exhibits distinct characteristics compared to other long bones. It exhibits more aggressive behavior with involvement of the entire length of the MC and expansion into the soft tissue. Literature reports an incidence of 1.7% for GCT of MC. Case Report: We report a 43-year-old female who visited the hospital with left hand swelling for 8 months that gradually progressed and localized mass over the dorsum of the medial aspect of the hand. MRI revealed an enchondroma-like benign bone lesion of the fourth MC in the meta diaphyseal area. The patient was scheduled for an en bloc excision with bone grafting from fibula with fusion of MC and MC phalangeal joints and K-wire fixation at the MC region. On exposure, the gross appearance revealed the lesion to be likely GT, and the histological findings confirmed the diagnosis of GCT, demonstrating multinucleated large cells and mononucleated stromal cells. Conclusion: The meta-diaphysis of small hand bone GCT is a rare occurrence at the site of MC. This case is hence reported for the same reason.